2014
DOI: 10.1002/2012pa002448
|View full text |Cite
|
Sign up to set email alerts
|

Surface water conditions and calcium carbonate preservation in the Fram Strait during marine isotope stage 2, 28.8-15.4 kyr

Abstract: [1] We present a high-resolution record of calcium carbonate preservation alongside the distribution pattern of planktic foraminifera from the Fram Strait. The record covers the marine isotope stage (MIS) 2, 28.8 to 15.4 kyr, including the Last Glacial Maximum (LGM) and the early deglaciation in multidecadal temporal resolution. The investigation is based on the distribution patterns of planktic foraminifera, stable isotopes, mean shell weight of Neogloboquadrina pachyderma, the degree of fragmentation of plan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
29
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 34 publications
(35 citation statements)
references
References 78 publications
(176 reference statements)
6
29
0
Order By: Relevance
“…Recently, a potential sea ice origin of brassicasterol (but not dinosterol) has been discussed by (Fig. 3) concur with the maximum abundance of the subpolar foraminifer T. quinqueloba in this core (Zamelczyk et al, 2014), which also points to a temporary retreat of sea ice. Coincident with this reduction in sea ice, a short but intensive discharge of glacial meltwater is recorded at various sites along the western continental slope of Svalbard, which caused a high accumulation of (terrigenous) organic matter (S1) and ice rafted detritus (Knies and Stein, 1998;Vogt et al, 2001;Jessen et al, 2010).…”
Section: The Late Glacial and Last Glacial Maximum (Lgm)supporting
confidence: 75%
See 3 more Smart Citations
“…Recently, a potential sea ice origin of brassicasterol (but not dinosterol) has been discussed by (Fig. 3) concur with the maximum abundance of the subpolar foraminifer T. quinqueloba in this core (Zamelczyk et al, 2014), which also points to a temporary retreat of sea ice. Coincident with this reduction in sea ice, a short but intensive discharge of glacial meltwater is recorded at various sites along the western continental slope of Svalbard, which caused a high accumulation of (terrigenous) organic matter (S1) and ice rafted detritus (Knies and Stein, 1998;Vogt et al, 2001;Jessen et al, 2010).…”
Section: The Late Glacial and Last Glacial Maximum (Lgm)supporting
confidence: 75%
“…3). Further, Zamelczyk et al (2014) observed a drop in the total foraminifer flux and a high shell fragmentation in the respective sediments of core MSM5/5-712-2 at about 19 ka BP which they attribute to a cooling of the sea surface. This onset of a perennial sea ice cover in eastern Fram Strait seems to coincide with the final expansion (according to Andersen et al, 1996) or retreat (see Jessen et al, 2010 for further references and discussion) of the SBIS at the western shelf edge of Svalbard.…”
Section: The Late Glacial and Last Glacial Maximum (Lgm)mentioning
confidence: 88%
See 2 more Smart Citations
“…The CaCO 3 content in surface sediments usually reflects the modern surface water oceanography and was, for example, successfully applied as a paleoceanographic tool to reconstruct northern Hemisphere glacial/interglacial cycles (e.g. Bond et al, 1992;Ruddiman and McIntyre, 1981;Zamelczyk et al, 2014). Furthermore, Faust et al (2016) recently revealed that Ca/Si and CaCO 3 in fjord sediments can provide detailed reconstructions of atmospheric circulation changes.…”
Section: Ca and Calcite: Marine Productivity Proxiesmentioning
confidence: 99%